Validation of the GALAD model and establishment of a new model for HCC detection in Chinese patients - Chen, Ping; Song, Haolin; Xu, Wei; Guo, Jin; Wang, Jianfei; Zhou, Juhong; Kang, Xiang; Jin, Chaolei; Cai, Yubo; Feng, Zixuan; Gao, Hainv; Lu, Fengmin; et al. (Frontiers in Oncology, 2022)
GALAD model is a model used to estimate the possibility of HCC in patients with chronic liver disease.However, whether this model can be used for Chinese patients remains to be determined. Our study was conducted to verify the performance of GALAD model in a Chinese population and construct a new model that is more appropriately for Chinese samples.There are total 445 patients enrolled in our study, and the GAADPB model was established by logistic regression.The new GAADPB model was powerful and stable, with better performance than the GALAD and other models，and it also was promising in the area of HCC prognosis prediction. Further study on the real-world HCC patients in China are needed.